2021
DOI: 10.1097/md.0000000000025100
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm, open-label, intervention study to investigate the improvement of glucose tolerance after administration of the 5-aminolevulinic acid (5-ALA) in the patients with mitochondrial diabetes mellitus

Abstract: Background: Mitochondrial diabetes mellitus (MDM) is characterized by maternal inheritance, progressive neurosensory deafness, insulin secretory disorder, and progressive microvascular complications. Mitochondria are critical organelles that provide energy in the form of adenosine triphosphate (ATP). An impairment of ATP production in pancreatic β cells is regarded as the main cause of the insulin secretory disorder in patients with MDM, and these patients require insulin replacement therapy early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Patient 1 was still dependent on insulin until 3 years old, but her plasma C‐peptide concentration was maintained at 0.3–0.6 ng/mL, and her HbA1c value was controlled at 7.0–7.5%. A recent study showed that mitochondrial supportive therapy of administration of 5‐aminolevulinic acid plus sodium ferrous citrate improved glycemic control in adult patients with mitochondrial diabetes mellitus (Nakamura et al, 2021). On the basis of the assumption that mitochondrial disease often presents with phenotypic variability, our patients may also have had improved glycemic control by improvement in insulin secretion and glucose tolerance by mitochondrial supportive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 1 was still dependent on insulin until 3 years old, but her plasma C‐peptide concentration was maintained at 0.3–0.6 ng/mL, and her HbA1c value was controlled at 7.0–7.5%. A recent study showed that mitochondrial supportive therapy of administration of 5‐aminolevulinic acid plus sodium ferrous citrate improved glycemic control in adult patients with mitochondrial diabetes mellitus (Nakamura et al, 2021). On the basis of the assumption that mitochondrial disease often presents with phenotypic variability, our patients may also have had improved glycemic control by improvement in insulin secretion and glucose tolerance by mitochondrial supportive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These results again verified that 5-ALA has an important role in blood, which may potentially influence the iron metabolism in body. The fact that 5-ALA serves as the universal precursor of heme metabolites may explain the mechanism [ 27 ]. However, heme is also an essential component of hemoglobin and has a catalytic and regulatory effect on cells, which plays a central role in terminal erythropoiesis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study design were published in the study protocol report [ 16 ]. The present study was a single-arm, open-label, interventional study carried out at Nagasaki University Hospital from August 2020 to October 2021.…”
Section: Methodsmentioning
confidence: 99%